The Effects of Kangaroo Care Applied by Turkish Mothers who Have Premature Babies and Cannot Breastfeed on Their Stress Levels and Amount of Milk Production - Coskun, Didem; Gunay, Ulviye (Elsevier Science Inc, 2020)
Purpose: This study aimed to examine the effects of kangaroo care applied by Turkish mothers who have premature babies and cannot breastfeed on their stress levels and amount of milk production. Design and methods: This open-label, multicentre, randomised controlled trial included preterm infants not breastfed by their mothers and the mothers of the infants. The mothers were randomised at a 1:1 ratio into the kangaroo care group and the standard care group. The mothers in the kangaroo care group applied kangaroo care to their babies once a day for three weeks. The mothers in the standard care group saw their infants for 15-20 min once a day for five days a week for three weeks, which was standard care in the newborn intensive care unit. The mothers milked their breasts with breast milking machines or pumps every day for three weeks. Results: The mothers in the kangaroo care group had higher breast milk production averages than the standard care group in all measurements. The mothers who applied kangaroo care had lower Parental Stressor Scale, subdimensions and total scale average scores than the mothers in the standard care group. Conclusions: Kangaroo care is effective at stimulating breast milk production and decreasing maternal stress levels. Practice implications: Kangaroo care decreases mothers' stress levels and increases breast milk production by mothers who cannot breastfeed their premature infants. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: breast milk; kangaroo care; mothers with premature infant; mother who cannot breastfeed; neonatal nurse